2017
DOI: 10.2320/matertrans.m2017011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Addition on the Precipitation Behavior in AZ91 Magnesium Alloy

Abstract: The effect of Sn (1, 3 and 5 mass%) addition on the precipitation behavior of AZ91 alloy has been investigated in the present study. The addition of Sn is effective in suppression of discontinuous precipitation as well as acceleration of continuous precipitation. The Mg 2 Sn particles at the grain boundary effectively reduce the nucleation sites for discontinuous β precipitates, and slow down the movement of the grain boundary. The addition of Sn remarkably enhances the aging response of AZ91. The hardness inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The coarse DP inhomogeneously distributed at the grain boundary, while the much smaller CP uniformly distributed inside grain. With increasing Sn content, the precipitation of Mg17Al12 phase was improved whilst the amount of Al atoms in the matrix was reduced [18]. The Mg2Sn precipitate was always accompanied by the divorced eutectic β-phase ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coarse DP inhomogeneously distributed at the grain boundary, while the much smaller CP uniformly distributed inside grain. With increasing Sn content, the precipitation of Mg17Al12 phase was improved whilst the amount of Al atoms in the matrix was reduced [18]. The Mg2Sn precipitate was always accompanied by the divorced eutectic β-phase ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Mg 2 Sn precipitates earlier from the melt during solidification process, and therefore could provide heterogeneous nuclei for Mg 17 Al 12 in eutectic reaction. Kim et al studied the solidification behavior of AZ91−xSn alloy (x = 1, 3, 5, mass%) and found that addition of Sn led to suppression of the discontinuous precipitation as well as significant improvement of hardness and strength [18]. However, Li's study showed that the hardness decreased with increasing Sn content from 0.5 to 1 mass%.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mg-Al-Sn (AT) alloys have been showing promise. The addition of Sn to Mg alloy has many advantages [5][6][7][8][9][10][11]. Sn causes solid solution strengthening (solubility of Sn in Mg is 14.85 wt.% at the eutectic temperature of 561 • C), precipitation strengthening, and creep performance at elevated temperatures in binary Mg-Sn alloys.…”
Section: Introductionmentioning
confidence: 99%